Brood desertion by female shorebirds: a test of the differential parental capacity hypothesis on Kentish plovers. - Amat, J A (2000)
The aim of this study was to examine whether the energetic costs of reproduction explain offspring desertion by female shorebirds, as is suggested by the differential parental capacity hypothesis. A prediction of the hypothesis is that, in species with biparental incubation in which females desert from brood care after hatching, the body condition of females should decline after laying to a point at which their body reserves are too low for continuing parental care. We tested this prediction on Kentish plovers (Charadrius alexandrinus) in which both sexes incubate but the females desert from brood care before the chicks fledge. We found no changes in either the body masses or body compositions of both individual male and female plovers from early incubation and throughout early chick rearing. Furthermore, the timing of brood desertion by females was not affected by their body condition. Neither did we find gender differences in the energetic costs of incubation. There were no differences in the timing of brood desertion between experimental and control females in an experiment in which we lengthened or shortened the duration of incubation by one week. These results indicate that energetic costs do not explain offspring desertion by female Kentish plovers and that the needs of chicks for parental care rather than cumulative investment by females is what determines the timing of brood desertion.